1985
DOI: 10.1007/bf00923144
|View full text |Cite
|
Sign up to set email alerts
|

Childhood depression: Peer reactions to depression and life stress

Abstract: The present study investigated children's responses to a peer's childhood depression. Younger children in third and fourth grade and older children in fifth and sixth grade were exposed to one of four films. The four films portrayed a female peer who was either depressed or not depressed and who had experienced numerous recent life stresses or no recent life stress. Overall, children rated the depressed peers as less likeable and attractive, as engaging in fewer positive current and future behaviors, and as ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
1
43
2
Order By: Relevance
“…In contrast, other coping behaviors (e.g., avoidance, use of alcohol) can be termed maladaptive because they do not lead to successful resolution of the stressful situation or to the long-term reduction of distress [62,63]. Specifically, coping through avoidance behaviors predicts poorer emotional outcomes in children [58], adolescents [63], and college students [45]. Given the extensive findings suggesting the importance of coping behaviors for the adjustment, coping behaviors should be another critical variable that is examined in the relationship between stress and adjustment.…”
Section: Coping Behaviorsmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, other coping behaviors (e.g., avoidance, use of alcohol) can be termed maladaptive because they do not lead to successful resolution of the stressful situation or to the long-term reduction of distress [62,63]. Specifically, coping through avoidance behaviors predicts poorer emotional outcomes in children [58], adolescents [63], and college students [45]. Given the extensive findings suggesting the importance of coping behaviors for the adjustment, coping behaviors should be another critical variable that is examined in the relationship between stress and adjustment.…”
Section: Coping Behaviorsmentioning
confidence: 86%
“…For example, denial or avoidance of a stressor could have negative effects on psychological adjustment [13], as avoidant coping is related to distress [57]. Further, avoidant coping is the most prominent strategy adopted by young adolescents who suffer from depression [58]. Thus, although avoidant coping is effective in the short-term for college students, escaping from problems inevitably leads to increased depressive affect in the long-term [19].…”
Section: Coping Behaviorsmentioning
confidence: 98%
“…Juvonen also concluded that ratings were generally more positive for hypothetical cases (as in the second study) than for actual classmates, which raises questions about the ecological validity of using imaginary vignettes. Peterson, Mullins, and RidleyJohnson (1985) examined childhood perceptions of the relationship between depression and stress. Groups of third to fourth graders and fifth to sixth graders viewed one of four videotape conditions featuring a 9-year-old girl displaying combinations of depressed/ nondepressed behaviors and stressful/ nonstressful causative conditions.…”
Section: Perceptions Of ;mentioning
confidence: 99%
“…Depressed children are less popular (Jacobsen, Lahey, & Strauss, 1983;Lefkowitz & Tesiny, 1985;Strauss, Forehand, Frame, & Smith, 1984), less liked (Blechman, et aI., 1986;Faust, Baum, & Forehand, 1985;Peterson, Mullins, & Ridley-Johnson, 1985), and are rejected by peers (Kennedy, Spence, & Hensley, 1989). Perhaps this is sensed by depressed youths and accounts for findings indicating that depressed youngsters engage in less social interaction (Kazdin, Esveldt-Dawson, Sherick, & Colbus, 1985).…”
Section: Behavioral Variables and Depression During Childhoodmentioning
confidence: 99%
“…In addition, it may lead to withdrawal (Kazdin et al, 1985), which insulates the young-steT from corrective learning experiences. As the youngster matures and faces new stressors, he or she does not have the family or peer social support (Blechman et aI., 1986;Jacobsen et aI., 1983;Kennedy et al, 1989;Peterson et al, 1985) necessary to help buffer their impact, and the impact is further heightened througb negative distortions in information processing (Kendall et aI., 1990) and a possible deficit in coping skills. Affect interacts with the previously mentioned variables in a reciprocal fashion.…”
Section: Clinical Significancementioning
confidence: 99%